Becoming Tornedalian - Keisu, Karin (Konstfack, Institutionen för Konst (K), 2022)
In this essay, I suggest a process of unlearning and decolonization from the perspective of a young Tornedalian woman without a mother tongue. I look at ideas of nationalism, assimilation, normativity, and homogeneity in Sweden through lived experience and memory, as well as academic research. I examine assimilation processes in Tornedalen in Sweden through academic theses by for example Lars Elenius, which I use to understand the impact that the workhouses and the ban of Meänkieli had in Tornedalen. I have read poetry by Nellie Wong and essays by for example Audre Lorde to further my understanding of how colonisation and assimilation impacts both the individual and the collective. Furthermore, this essay includes how this relates to my artistic practise and my master of the Arts project Back to Back (2022), which is part of a long-term project I am working on in collaboration with Josse Thuresson.